Music in the Film Adaptation of La noche de la Usina by Eduardo Sacheri - Caño Rivera, Claudia (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper analyzes the soundtrack in the movie Heroic Losers, and how it functions as an adaptation of the novel La noche de la Usina. We will use the methodology proposed by Patrick Cattrysse —an important scholar of adaptation studies who focus of the pragmatic outlook of film daptation. Thus, we will analyze two main areas: the contribution of music in the recreation of western elements from the novel to the film, and its function to adapt the film to a target audience, which, in this case, would be the contemporary Argentinian society. Finally, we will conclude our work with a reflection on the impact that music has in the transfer from the literature to the cinema.